PERILAKU POLITIK PEREMPUAN TANI DALAM PILKADA LANGSUNG: Studi di Kecamatan Konda Kabupaten Konawe Selatan - Syaifudin Suhri Kasim (Halu Oleo University, 2024)
This study aims to explore deeper the motivations, attitudes, and political preferences of women farmers in direct regional elections, and how social, economic, and cultural factors influence their political behaviour. This study is a qualitative descriptive study, with a case study approach. This study uses a qualitative research method. The methods used to collect data in this study are: observation, interviews and documentation. The results of the study indicate that the motivations, attitudes, and political preferences of women farmers in direct regional elections are greatly influenced by social, economic, and cultural factors. The majority of women farmers choose candidates who are considered capable of supporting family needs and improving community welfare. Their political attitudes are also shaped by their life experiences, social interactions, and roles in the family. Policies that focus on the economic empowerment of women farmers, such as increasing employment opportunities or skills training programs, often attract their attention. These preferences are not only the result of urgent needs but also a reflection of women farmers' aspirations to improve the standard of living of their families and their environment.